(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2012)
Positive law is a being whose character cannot be searched for in a world of conditioned and changeable matter. On the assumption that the spiritual being constitutes the most perfect sphere of existence, the conviction emerges that the law also has its fundamental being in the spirit. The spiritual force of legal norms consists in the fact that they are known, understood, and needed as rules of conduct. The internal unity and harmony of a human being manifest themselves in establishing and obeying positive law, which is true to the spirit.